Spirituality in The Workplace and Employee Performance: A Literature Perspective - Safrizal, Helmi Buyung Aulia; Eliyana, Anis; Gunawan, Sri (International Journal of Psychosocial Rehabilitation, 2020)
The concept of spirituality has attracted various parties to implement it in various organization sectors. Based on the results of literature review, implementation of spirituality concept in workplace brings a variety impacts on the organizational life such as increase employee commitment, increase retention of employees, increase employee satisfaction, stress reduction, and increase the productivity and performance of individuals, organizational units, and organizations as a whole. This article attempts to review the literature and discuss relationship between spirituality in the workplace and employee performance.